2020
DOI: 10.1080/17549507.2020.1769728
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of speech-language pathologists’ intervention and intensity provision for children with phonological impairment

Abstract: Purpose: To explore the reasons behind speech-language pathologists' (SLPs') current clinical practices (intervention and intensity provision) for children (0-18 years) with phonological impairment.Method: Three focus groups each with five SLPs and six 1:1 interviews with SLP managers from one region of the UK (n=21) were carried out. A thematic analysis was undertaken.Results: SLPs often used an eclectic mix of familiar approaches with easily-accessible therapy materials. SLPs only reported deviating from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…It is widely reported that SLPs frequently adopt an eclectic therapy approach (Brumbaugh & Smit, 2013;Hegarty et al, 2020;Joffe & Pring, 2008;McLeod & Baker, 2014;Oliveira et al, 2015;Pascoe et al, 2010;Roulstone & Wren, 2001) rather than a single approach. An eclectic approach involves blending different therapy approaches or elements of different methods (Lancaster et al, 2010;McLeod & Baker, 2014).…”
Section: Therapy Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…It is widely reported that SLPs frequently adopt an eclectic therapy approach (Brumbaugh & Smit, 2013;Hegarty et al, 2020;Joffe & Pring, 2008;McLeod & Baker, 2014;Oliveira et al, 2015;Pascoe et al, 2010;Roulstone & Wren, 2001) rather than a single approach. An eclectic approach involves blending different therapy approaches or elements of different methods (Lancaster et al, 2010;McLeod & Baker, 2014).…”
Section: Therapy Approachesmentioning
confidence: 99%
“…The external scientific evidence for SSDs relating to target selection, therapy approaches, and (to a lesser extent) the structural and procedural aspects of therapy sessions has been well considered within the EBP framework; less has been done on the professional and clinical expertise side of the EBP triangle to privilege the voices of SLPs working in this area of practice (Hegarty et al, 2020). The aim of the current study was to gain an in-depth insight into the intervention processes used by SLPs for treating children with SSDs.…”
Section: Structural and Procedural Aspects Of Therapy Sessionsmentioning
confidence: 99%
See 3 more Smart Citations